Think About Editing : A Grammar Editing Guide for ESL Writers - Ascher, Allen (Heinle1993, 1993)
Think About Editing is designed to help intermediate to advanced level students of ESL and EFL learn to edit their writing for errors in grammatical structure and usage. This tasked-based, student-centered text heightens the student's awareness of general linguistic rules so that he or she can learn to repair, and ultimately avoid , many of the errors commonly found in student writing. Interactive in approach, it strikes up a dialogue with the student, encouraging him or her to analyze language samples and discover these rules, and then apply them to his or her own writing.